Comparison of Kinematics and Muscle Activation between Push-up and Bench Press - Tillaar, Roland van den (Sports Medicine International Open, 2019)
The purpose of this study was to compare the similarity in kinematics and upper-body muscle activation between push-up and bench press exercises over a range of loads. Twenty resistance-trained subjects (age 22.5±5.24 yrs, body mass 83.7±10.7 kg, height 1.80±0.06 m) executed bench presses and push-ups with 4 different loads. Bench press was executed at 50–80% of their assumed 1 repetition max in steps of 10 kg, while push-ups were executed without a weight vest and with a 10–20–30 kg weight vest. A linear encoder measured kinematics (displacement, time, average and peak velocity) during the exercises at each load, together with mean and maximal muscle activation of 8 upper body muscles and their timing for each exercise and each load. The main findings of this study demonstrate no differences in kinematics and muscle activation between the two exercises and that the different loads had the same effect upon both push-up and bench press in experienced resistance-trained men. For coaches and athletes, push-ups and bench presses for strength training can be used interchangeably. By using a weight vest, push-ups can mimic different loads that are similar to different intensities in the bench press that can be used to train strength demands.
Keywords: peak velocity; mean velocity; resistance training; strength